Rekonstruksi Pemberian Amnesti dan Abolisi dalam Kritik Terhadap Kewajiban Pertimbangan DPR Berdasarkan Pasal 14 Ayat (2) UUD NRI 1945 - alex prayoga sidabutar (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Indonesia as a country of law means that all aspects of life must be based on law. The President has the prerogative to grant amnesty and abolition, but since the amendment to the 1945 Constitution, this must be considered by the DPR in accordance with Article 14 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. This research was conducted to determine how the President's power to grant amnesty and abolition is exercised, as well as its impact on the legal and justice system in Indonesia. The results of the research show that the president should grant amnesty based on the consideration of the Supreme Court (MA) and not on the basis of consideration (DPR) because the government institution that plays a role in the legal field or realm is the MA while the DPR plays a role in the political field or realm.